Analisis Corporate Value Dalam Menignkatkan Kinerja Karyawan di Aston Pasteur Hotel Bandung - Audrey Indira Eka Putri; Fenny Damayanti; Agus Garnida (Akademi Sekretari Manajemen Taruna Bakti, 2023)
Corporate values ​​are very important in a company, especially in the hospitality sector, especially at the Aston Pasteur Hotel Bandung. long-term goals in the company. The method used in this study is a qualitative method or based on existing data and theory, which is in accordance with the Aston Pasteur Bandung Corporate Values ​​Guidelines, besides that it can also be seen or analyzed from the daily life of the staff whether they apply the Company Values. or not in the Aston Pasteur environment. From this Company Value Analysis, it can be concluded that Corporate Value has a very important role for Aston Pasteur in order to encourage Aston Pasteur to further develop and advance, because guests who come to Aston Pasteur Hotel will assess and see how the overall way or behavior of the staff in serving, can be seen from small things such as friendliness, enthusiasm to serve guests, service excellence and others. How important is Corporate Values ​​to improve employee performance at the Hotel, namely Aston Pasteur Bandung, so that Aston can develop and be known by many people and trusted by consumers. Therefore, it can be concluded that Corporate Values ​​Analysis is very influential on employee performance, especially at Aston Pasteur Hotel Bandung.